2012
DOI: 10.1017/s1074070800024081
|View full text |Cite
|
Sign up to set email alerts
|

From Coffee Beans to Microchips: Export Diversification and Economic Growth in Costa Rica

Abstract: During the early 1980s Costa Rica experienced its worst economic crisis since World War II, which led to the abandonment of the import substitution model of development adopted in the 1960s. This severe economic downturn also spurred the implementation of a series of new policies supporting foreign investment in high-value-added industries and the diversification of the nation's exports. As a result, Costa Rica has diversified its economic activity, moved away from its historical dependence on agricultural exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…Cadot, Carrere, and Strauss-Khahn (2011) showed that exports promote reduced production diversification. Ferreira and Harrison (2012) indicated that no long-run relationship was found between export diversification and economic growth. There is no consensus for that relationship.…”
Section: Existing Studiesmentioning
confidence: 99%
“…Cadot, Carrere, and Strauss-Khahn (2011) showed that exports promote reduced production diversification. Ferreira and Harrison (2012) indicated that no long-run relationship was found between export diversification and economic growth. There is no consensus for that relationship.…”
Section: Existing Studiesmentioning
confidence: 99%
“…The research of Bebczuk and Berrettoni [21] showed that the increase of export variety in Latin American countries did not lead to GDP expansion. Ferreira and Harrison [22] showed that there was no long-term relationship between Costa Rica's export variety and economic growth. Some other studies concluded that there was a "U"-shaped curve relationship between export variety and economic growth [23][24][25].…”
Section: Export Variety and Economic Growthmentioning
confidence: 99%
“…We will follow the model used by Ferreira and Harrison (2012). They used the simple neoclassical production function to study the growth process.…”
Section: Impact Of Export Diversification On Economic Growthmentioning
confidence: 99%